2023
DOI: 10.1161/circinterventions.122.012332
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Clinical Outcome of the Biodegradable Polymer Ultrathin Strut Sirolimus-Eluting Stent Compared to the Biodegradable Polymer Biolimus-Eluting Stent in Patients Treated With Percutaneous Coronary Intervention: From the SORT OUT VII Trial

Abstract: Background: Biodegradable polymer drug-eluting stents were developed to improve safety and efficacy outcomes for patients undergoing percutaneous coronary intervention. However, few long-term follow-up efficacy studies are available. The study sought to investigate 5-year results from the SORT OUT VII trial (Scandinavian Organization for Randomized Trials With Clinical Outcome) comparing the biodegradable polymer ultrathin-strut sirolimus-eluting Orsiro stent (O-SES) versus the biodegradable polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Although the Orsiro SES has been thoroughly investigated, only few studies have assessed the long‐term clinical outcome after PCI with this stent in all‐comers: The most recently published randomized clinical trial that reported 5‐year follow‐up data (SORT OUT VII) compared the Orsiro SES with the Nobori biodegradable polymer biolimus‐eluting stent (Terumo Corporation) 13 . In that trial, the composite primary endpoint TLF did not differ between the Orsiro SES and Nobori biolimus‐eluting stent groups (12.4% vs. 13.1%), and it was similar to our findings in the Orsiro SES group (12.0%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Orsiro SES has been thoroughly investigated, only few studies have assessed the long‐term clinical outcome after PCI with this stent in all‐comers: The most recently published randomized clinical trial that reported 5‐year follow‐up data (SORT OUT VII) compared the Orsiro SES with the Nobori biodegradable polymer biolimus‐eluting stent (Terumo Corporation) 13 . In that trial, the composite primary endpoint TLF did not differ between the Orsiro SES and Nobori biolimus‐eluting stent groups (12.4% vs. 13.1%), and it was similar to our findings in the Orsiro SES group (12.0%).…”
Section: Discussionmentioning
confidence: 99%
“…So far, no 5-year results have been published for the Onyx ZES, while a few all-comer trials have reported 5-year outcomes for the Orsiro SES. [13][14][15] Therefore, in this final report of the BIONYX trial, we analyzed for the first time the 5-year follow-up data, comparing all-comers treated with Onyx ZES versus Orsiro SES. In addition, we performed a prespecified subgroup analysis in patients with known diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the multilayer absorbable PLGA coating completely degrades in vitro in approximately 8 weeks, immediately after complete elution of the drug (4,23). In addition to these, there are many studies demonstrating that biodegradable polymer coated sirolimus-eluting stents are both safe and feasible in preventing restenosis in human or experimental animal models (24)(25)(26)(27). The metal structure of Atlas drug-eluting stents enables the stent to be prepared with a very thin support structure and allows radioopacity (8,28).…”
Section: Discussionmentioning
confidence: 99%
“…In the SORT OUT (Scandinavian Organisation for Randomized Trials with clinical Outcome) VII trial the biodegradable ultrathin strut sirolimus-eluting stent (Orsiro; Biotronik) (O-SES) was compared to the biodegradable polymer biolimus-eluting stent (Nobori; Terumo) (N-BES) regarding target lesion failure (TLF). [11][12][13] This study aimed to assess the long-term outcomes for O-SES and N-BES in an all-comer patient population with particular attention to the ACS subgroup.…”
Section: Introductionmentioning
confidence: 99%